Ausência de detecção de Xanthomonas axonopodis pv. malvacearum em sementes de algodoeiro usadas na região nordeste de Mato Grosso do Sul, em um estudo de três safras agrícolas - Theodoro, Gustavo de Faria; Correia, Hectory de Castro; da Silva, Rafael Rodrigues; Chumpati, André Augusto; Cortina, Josiane Vogel; Maringoni, Antonio Carlos [UNESP] (My University, 2014)
The aim of this work was to evaluate the presence of the causal agent of angular leaf spot, Xanthomonas axonopodis pv. malvacearum, in 38 cotton seeds samples with or without linter used in the northeast region of Mato Grosso do Sul, Brazil, during the crop seasons of 2008/09, 2009/10 e 2010/11. It was used the semi selective culture media MSSXAN (beef extract - 3 g, peptone - 5 g, soluble starch - 10 g, sucrose - 5g; Tween 80 - 10 mL; CaCl2 - 0.25 g; crystal violet solution at 1% - 150 mL; cephalexin - 50 mg; chlorothalonil - 10 mg; methyl thyophanate - 10 mg; agar - 15 g; sterile distilled water - 1000 ml) for the isolation of the bacteria and the suspect colonies of being X. axonopodis pv. malvacearum were purified and submitted to the Gram stain, potassium hydroxide and pathogenicity tests in the leaves of cotton plants of the susceptible genotype NC 53345. The presence of X. a. pv. malvacearum was not detected in the evaluated seed samples.
Absence of detection of Xanthomonas axonopodis pv. malvacearum in cotton seeds used in the northeast region of Mato Grosso do Sul in a three-based crop season study
Keywords: Dissemination; Gossypium hirsutum; Seed pathology